The relationship between interpersonal emotion regulation and interpersonal competence controlled for emotion dysregulation - Malkoç, Asude; Aslan Gördesli, Meltem; Arslan, Reyhan; Çekici, Ferah; Aydın Sünbül, Zeynep (Sciedu Press, 2019)
The aim of this study is to examine the role of interpersonal emotion regulation on interpersonal competency when controlled for emotion dysregulation. The sample of the study consists of 342 (235 female; 107 male) undergraduate students attending to the various departments of a private university in Turkey. The average age of participants was 20.81 (SD=2.29). The Interpersonal Emotion Regulation Scale, Difficulties in Emotion Regulation Scale and Interpersonal Competency Scale were used. Analyses were conducted through the SPSS 20 (IBM, 2011). Results of hierarchical regression analysis revealed that interpersonal emotion regulation and emotion dysregulation seem to predict interpersonal competency. After controlling for the effect of emotion dysregulation, interpersonal emotion regulation alone explains 18% of the overall variance in interpersonal competency. Interpersonal emotion has the highest contribution on interpersonal competency followed by emotion dysregulation.
Keywords: Emotion Dysregulation; Interpersonal Competency; Interpersonal Emotion Regulation; University Students